(untitled) (PETITUM, 2025)
This study aims to determine the effectiveness of Civil Servant Investigators (PPNS) in handling administrative violation cases in the City of Balikpapan and to identify the factors that influence the effectiveness of Civil Servant Investigators (PPNS) in handling administrative violation cases in the City of Balikpapan. This study employs a normative legal research method, focusing on legislation, legal principles, and legal doctrines governing the role of PPNS in administrative investigations. The research findings indicate that, regarding the effectiveness of Civil Servant Investigators (PPNS) in handling administrative violations in Balikpapan City, it can be concluded that the role of PPNS is currently not functioning optimally. Although, in theory, PPNS have the authority to conduct investigations into administrative violations across various sectors such as the environment, labor, and licensing, in practice they face various obstacles, including a lack of coordination between agencies, weak institutional support, and limited enforcement authority. The effectiveness of the PPNS is also hampered by overlapping regulations, unclear procedures between agencies, and a lack of integration in the monitoring and reporting systems.